2020
DOI: 10.1038/s41419-020-02900-4
|View full text |Cite
|
Sign up to set email alerts
|

PGAM1, regulated by miR-3614-5p, functions as an oncogene by activating transforming growth factor-β (TGF-β) signaling in the progression of non-small cell lung carcinoma

Abstract: Phosphoglycerate mutase 1 (PGAM1) is a recently identified key catalytic enzyme in aerobic glycolysis. Recent literature has documented that dysregulated PGAM1 expression is associated with tumorigenesis in various cancers. However, the expression status and biological function of PGAM1 in non-small-cell lung cancer (NSCLC) are poorly elucidated. In this study, we found that PGAM1 was overexpressed in NSCLC tissues and that high expression of PGAM1 was associated with poor prognosis in NSCLC patients. Function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…MiR-3614-5p displayed low expression in HCC tissues and cells and overexpression of miR-3614-5p totally reversed the inhibitory effect of LOXL1-AS1 knockdown on HCC cell malignant behaviors. It has been reported that miR-3614-5p could repress cell proliferation and invasion of non-small cell lung cancer [ 33 ], which further supported the anti-tumor role of miR-3614-5p in HCC cells.…”
Section: Discussionmentioning
confidence: 60%
“…MiR-3614-5p displayed low expression in HCC tissues and cells and overexpression of miR-3614-5p totally reversed the inhibitory effect of LOXL1-AS1 knockdown on HCC cell malignant behaviors. It has been reported that miR-3614-5p could repress cell proliferation and invasion of non-small cell lung cancer [ 33 ], which further supported the anti-tumor role of miR-3614-5p in HCC cells.…”
Section: Discussionmentioning
confidence: 60%
“…Tumortargeted glycolysis is considered a potential therapeutic strategy for tumor targeting. PGAM1 is a key enzyme for glycolysis, and a large number of studies suggest that PGAM1 is closely related to the malignant progression of tumors [10][11][12][13]. However, whether PGAM1 has a regulatory role in breast cancer remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…13 PGAM1 is highly expressed in various tumors, such as oral squamous cell carcinoma, prostate cancer, non-small cell lung cancer, renal clear cell carcinoma, pancreatic ductal carcinoma, and colorectal cancer, and is associated with tumor invasion, migration, and proliferation. [14][15][16][17][18][19] The present study showed that ENO1 and PGAM1 are highly expressed in MM. Understanding the cooperative mechanism by which ENO1 and PGAM1 affect MM development is our next research direction.…”
Section: Discussionmentioning
confidence: 92%